2019
DOI: 10.1002/ijfe.1742
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Fama–French factors' predictability with Bayesian modelling and copula‐based portfolio optimization

Abstract: This study is investigating the predictability of the five Fama–French factors and explores their optimal portfolio allocation for factor investing during 2000–2017. Firstly, we forecast each factor with a pool of linear and nonlinear models. Next, the individual forecasts are combined through dynamic model averaging, and their performance is benchmarked by the best performing individual predictor and other forecast combination techniques. Finally, we use the generalized autoregressive score model and the skew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 85 publications
1
3
0
Order By: Relevance
“…Although SVR sets are inferior to XGB in terms of out‐of‐sample performance, their predictive power is better than other models. The result is in line with several studies that suggest SVR can be a robust prediction tool supporting individual predictors (Sermpinis et al, 2014; Zhao et al, 2019). Finally, although LSTM falls short of the GBDT family, it has more accurate results than the benchmark, in line with recent experiments in BTC prediction (Ji et al, 2019; McNally et al, 2018).…”
Section: Statistical Performancesupporting
confidence: 91%
See 2 more Smart Citations
“…Although SVR sets are inferior to XGB in terms of out‐of‐sample performance, their predictive power is better than other models. The result is in line with several studies that suggest SVR can be a robust prediction tool supporting individual predictors (Sermpinis et al, 2014; Zhao et al, 2019). Finally, although LSTM falls short of the GBDT family, it has more accurate results than the benchmark, in line with recent experiments in BTC prediction (Ji et al, 2019; McNally et al, 2018).…”
Section: Statistical Performancesupporting
confidence: 91%
“…For both sets of factors (RFE-RF and PCA), we shed light on the predictive power of the GBDT family (XGB and LBM) because of all the negative statistics of the MDM test. Zhao et al (2019) suggested that when the superiority of forecasting models suffers from data-snooping bias, the predictive performance may be attributed to luck. In order to further validate the superiority of the XGB model, we then apply two statistical tools, namely, the SPA test and the MCS test.…”
Section: Statistical Performancementioning
confidence: 99%
See 1 more Smart Citation
“…In order to solve the asset pricing puzzle, Fama and French [1] proposed the three-factor model, where the crosssectional variation in average portfolio returns is explained by the excess return of a portfolio, the stock size, and the book-to-market ratio. After this pioneering study, scholars proposed different types of factor models from different perspectives and tested them [3,[13][14][15][16][17][18][19][20]. For example, Lam and Tam [14] investigated the role of liquidity in pricing stock returns and found that the liquidity four-factor model is the best model to explain stock returns in the Hong Kong stock market.…”
Section: Literature Reviewmentioning
confidence: 99%